2021
DOI: 10.1177/10775463211019213
|View full text |Cite
|
Sign up to set email alerts
|

Delamination effects on the unsteady aero-elastic behavior of composite wing by modal analysis

Abstract: This article deals with the investigation of delamination effects on the flutter behavior of a composite wing subjected to unsteady aerodynamic loads by providing an integrated procedure using exact methods. For this purpose, an undamaged wing structure is modeled as a cantilevered Bernoulli–Euler beam with coupled bending–torsion and delaminated wing structure is modeled as three interconnected intact beams. The modal analysis of the intact and delaminated beams is performed and mode shapes are obtained based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
(50 reference statements)
0
2
0
Order By: Relevance
“…The presence of delamination can have a positive and negative influence on the flutter and divergence velocity. 62 Based on the above literature survey, it is found that the presence of delamination can have disastrous effects on the aeroelastic response of the structures. Manufacturing defects are one of the major causes of delamination and the process involved in the manufacturing of composite plates with VAT laminates are much more complicated than constant stiffness laminates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of delamination can have a positive and negative influence on the flutter and divergence velocity. 62 Based on the above literature survey, it is found that the presence of delamination can have disastrous effects on the aeroelastic response of the structures. Manufacturing defects are one of the major causes of delamination and the process involved in the manufacturing of composite plates with VAT laminates are much more complicated than constant stiffness laminates.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of delamination can have a positive and negative influence on the flutter and divergence velocity. 62…”
Section: Introductionmentioning
confidence: 99%